The distribution of mycosporine-like amino acids in phytoplankton across a Southern Ocean transect - Weiss, Elliot L.; Cape, Mattias Rolf; Pan, B. Jack; Vernet, Maria; James, Chase C.; Smyth, Tim J.; Ha, Sun-Yong; Iriarte, José L.; Mitchell, B. Greg (Frontiers in Marine Science, 2022)
Interactions between phytoplankton and ultraviolet radiation (UVR: 280 – 400 nm) are undergoing changes dictated by variability in ocean temperature, the depth of mixed layers, nutrient availability, and the thickness of the ozone layer. There are a variety of mechanisms for phytoplankton to cope with UVR stress, one of the most prevalent being the presence of mycosporine-like amino acids (MAAs). Despite the importance of these molecules to phytoplankton fitness under UVR stress, knowledge of the diversity and distribution of these molecules in the world’s oceans is relatively limited. Here, the composition and distribution of MAAs in phytoplankton were examined in a transect across the Southern Ocean, crossing multiple fronts, from eastern New Zealand to the West Antarctic Peninsula in March and April of 2018. The highest concentration of MAAs (> 0.2 μg/L) was found between 50 and 60 °S, as well as along a longitudinal gradient between 137.47 and 144.78 °W. A strong correlation was found between a model of the preceding month’s UVR dosage experienced in the mixed layer and the ratio of MAAs to chlorophyll-a across the transect, indicating a relationship between the integrated history of light exposure and phytoplankton physiology. Haptophytes accounted for the majority of biomass north of the polar front (PF) and were strongly correlated with a diversity of MAAs. South of the PF a transition to a community dominated by diatoms was observed, with community composition changes strongly correlated to porphyra-334 concentrations. The data presented here provide a baseline for MAA abundance and association with specific phytoplankton taxa across the Southern Ocean amid a changing climate.